OPTIMIZATION OF Bacillus cereus GROWTH IN MEDIA WITH DIFFERENT CARBON SOURCES - Putra, Muhammad Hendra; Feliatra, Feliatra; Effendi, Irwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Bacillus cereus is a probiotic bacteria that requires media as a source of nutrients for its growth. This study aims to the media used were tofu liquid waste, sago liquid waste, and molasses. The method used is an experimental method, namely testing two groups of bacterial isolates; B. cereus SN7 and the consortium (combination of five isolates from B.cereus with different strains). Each group of isolates was grown with three replications on each waste medium. bacterial growth every six hours for twenty four hours using two methods; Total Plate Count (TPC) and bacterial cell biomass. There was no significant difference in growth between the two groups of bacterial isolation. The optimal growth of each isolate was found in molasses waste. The growth between two bacterial isolates in the liquid waste media was B. cereus SN7 bacterial isolate.